2017
DOI: 10.1007/s00253-017-8306-5
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the horizontal transfer of functional genes as a suitable approach for evaluation of the bioremediation potential of petroleum-contaminated sites: a mini-review

Abstract: Petroleum sludge contains recalcitrant residuals. These compounds because of being toxic to humans and other organism are of the major concerns. Therefore, petroleum sludge should be safely disposed. Physicochemical methods which are used by this sector are mostly expensive and need complex devices. Bioremediation methods because of being eco-friendly and cost-effective overcome most of the limitations of physicochemical treatments. Microbial strains capable to degrade petroleum hydrocarbons are practically pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 57 publications
0
20
0
Order By: Relevance
“…Plasmids play a major role in bacterial genetic diversity (2), evolution (3), and adaptation (4). Conjugative exchange (i.e., the transfer of plasmids from one bacterium to another) can lead to the spread of a variety of functions, including degradation of heavy metals and anthropogenic toxic waste (5), bacteriocin and toxin production to ward off predators (6), and, alarmingly, antibiotic resistance and virulence plasmids that inhibit antibiotics and lead to novel and untreatable diseases (7). Plasmids are also extensively used as tools in genetic engineering (8).…”
Section: Announcementmentioning
confidence: 99%
“…Plasmids play a major role in bacterial genetic diversity (2), evolution (3), and adaptation (4). Conjugative exchange (i.e., the transfer of plasmids from one bacterium to another) can lead to the spread of a variety of functions, including degradation of heavy metals and anthropogenic toxic waste (5), bacteriocin and toxin production to ward off predators (6), and, alarmingly, antibiotic resistance and virulence plasmids that inhibit antibiotics and lead to novel and untreatable diseases (7). Plasmids are also extensively used as tools in genetic engineering (8).…”
Section: Announcementmentioning
confidence: 99%
“…Horizontal gene transfer, which allows bacteria acquire exogenous genes from foreign species, is necessary for bacteria to survive in and adapt to harsh environmental conditions ( Lawrence, 1997 ; Molbak et al, 2003 ). It has been pointed that horizontal gene transfer plays a vital role in the bioremediation of soils contaminated with petroleum hydrocarbons ( Shahi et al, 2017 ). Li et al (2017) also found that the phenanthrene degraders revealed by the 16S rRNA genes and the polycyclic aromatic hydrocarbons-ring hydroxylating dioxygenase (PAH-RHD) genes were different, and they speculated that horizontal gene transfer and hybridization might have occurred.…”
Section: Discussionmentioning
confidence: 99%
“…The first is that few independent microbial ecosystems are available in natural habitats for investigating these patterns because the predation and migration of mixed macroorganisms alter the structure of the microbial community (Jousset, ; Buchkowski et al ., ). The other challenge is that these patterns could not be investigated just based on the phylogenetic diversity and dynamics of microbial ecosystems because of the undetermined relationships between species and their functions due to frequent horizontal gene transfer (Fuhrman, ; Devictor et al ., ; Shahi et al ., ). The oil reservoir habitat is a relatively closed microbial ecosystem in which the essential nutrients of heterotrophic microorganisms are scarce except for hydrocarbons, including saccharides, alcohols and volatile fatty acids (Head et al ., ; Brown, ; Harner et al ., ; Siegert et al ., ; Patel et al ., ).…”
Section: Introductionmentioning
confidence: 99%